(untitled) (Indian Journal of Nematology, 2025)
Entomopathogenic nematodes (EPNs) from the families Steinernematidae and Heterorhabditidae offer effective biological control of several soil insect pests as a biological component of the Integrated Pest Management (IPM) programmes. This study evaluated the field efficacy of inundative applications of Steinernema carpocapsae against Leucopholis coneophora, in root grubinfested arecanut gardens of Bare village in Kasaragod district of Kerala, India. Biannual applications of S. carpocapsae at 2×106 infective juveniles (IJs) per palm over three years (2015–2016 to 2017–2018) significantly reduced mean root grub populations from 7.22 to 2.19 larvae per palm, while arecanut yield increased by an average of 122.43 per cent in the nematode-treated plots compared to the control (farmer’s practice). EPNs were re-isolated from 42.5 per cent of treated soil samples, indicating successful nematode establishment and recycling. These results suggest that native strains of S. carpocapsae are effective components of IPM strategies for long-term insect suppression.